Citizen emperor Napoleon in power - Dwyer, Philip G. (Yale University Press, 2013)
Dwyer explores the young leader's reign, complete with mistakes, wrong turns, and pitfalls, and reveals the great lengths to which Napoleon goes in the effort to fashion his image as legitimate and patriarchal ruler of the new nation.